2012
DOI: 10.1111/j.1474-9726.2012.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

The number of p16INK4a positive cells in human skin reflects biological age

Abstract: Summary Cellular senescence is a defense mechanism in response to molecular damage which accumulates with aging. Correspondingly, the number of senescent cells has been reported to be greater in older than in younger subjects and furthermore associates with age-related pathologies. Inter-individual differences exist in the rate at which a person ages (biological age). Here, we studied whether younger biological age is related to fewer senescent cells in middle- aged individuals with the propensity for longevit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(213 citation statements)
references
References 24 publications
(27 reference statements)
9
185
1
1
Order By: Relevance
“…In contrast to nevus melanocytes, these cells always appeared to lack expression of proliferation-promoting Wnt target genes. Significantly, previous studies have identified similarly positioned p16-expressing cells in the epidermis, morphologically resembling melanocytes, whose abundance increases with age (53,54). The trigger of p16 expression in these epidermal melanocytes, be it age-associated acquisition of an activated oncogene or another mode of stress, and the relationship, if any, of these cells to melanoma remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to nevus melanocytes, these cells always appeared to lack expression of proliferation-promoting Wnt target genes. Significantly, previous studies have identified similarly positioned p16-expressing cells in the epidermis, morphologically resembling melanocytes, whose abundance increases with age (53,54). The trigger of p16 expression in these epidermal melanocytes, be it age-associated acquisition of an activated oncogene or another mode of stress, and the relationship, if any, of these cells to melanoma remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There is now strong evidence that cellular senescence is a potent anticancer mechanism (39)(40)(41)(42). In contrast, despite its name, its discovery over 50 years ago, and increasing data associating senescent cells with aging phenotypes and age-related pathology (43)(44)(45)(46)(47)(48)(49)(50), evidence has only recently emerged showing that eliminating senescent cells can actually delay age-related dysfunction (51), at least in a progeroid mouse model. This finding still must be tested in chronologically aged models, but this is the first clear evidence that senescent cells are important drivers of multiple age-related pathologies.…”
Section: Cellular Senescencementioning
confidence: 99%
“…The abundance of senescent cells increases in multiple tissues with chronological aging and in progeroid syndromes (43,47,50,(52)(53)(54)(55). Several processes have been identified that cause or are associated with cellular senescence, all of which also increase with age ( Figure 3).…”
Section: Cellular Senescencementioning
confidence: 99%
“…(65) Cellular senescence, as one basic process that play most contribution to age-related dysfunction and chronic sterile inflammation, refers to the essentially irreversible growth arrest that occurs when cells experience potentially oncogenic insults (58,(130)(131)(132)(133)(134), and now believe that it was the potent anticancer mechanism (135)(136)(137)(138). In contrast, despite its name, its discovery over 50 years ago, and increasing data associating senescent cells with aging phenotypes and age-related pathology (59,(139)(140)(141)(142)(143)(144)(145), while eliminating senescent cells could delay age-related dysfunction (146), at least in a progeroid mouse model. Cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) are clearly related to age and can reduced life span.…”
Section: Telomeres and Diseasesmentioning
confidence: 99%